Substrates and Growth-Promoting Rhizobacteria in the Germination and Nursery Establishment of Passiflora edulis Sims (Passion Fruit) - Carranza-Patiño, Mercedes Susana; Pérez-Zambonino, Yomaira Aracely; Reyes-Perez, Juan José; Coello-Cevallos, Wilson Jose; Espinoza-Torres, Mary Cruz (REVISTA TERRA LATINOAMERICANA, 2025)
The study evaluated the ef fect of dif ferent substrates and growth-promoting rhizobacteria on the germination and nursery development of Passiflora edulis Sims (passion fruit). The research was conducted at the Quevedo State Technical University, Ecuador, and was divided into two phases: germination and nursery growth. Four rhizobacteria were used (Serratia marcescens, Pseudomonas protegens, Enterobacter absuriae, and Acinetobacter calcoaceticus) at a concentration of 1 × 10⁸ CFU mL-1, in combination with three substrates (mountain soil with perlite, organic peat with perlite, and a mixture of both). E. absuriae achieved a germination rate of 51.11%, similar to the control, while P. protegens was particularly ef fective in promoting a leaf area of 12.92 cm², root length of 11.61 cm, and stem diameter of 1.33 millimeters. A. calcoaceticus, in mountain soil with perlite, promoted remarkable growth with 8 leaves per plant, a height of 14.72 cm, and a dry mass weight of 0.3 g. High catalase enzymatic activity was observed in treatments with E. absuriae, along with a significant increase in antioxidants in S. marcescens in the mountain soil with perlite substrate, accompanied by a bacterial density of 1.19 × 10⁸ CFU. The study highlights the potential of rhizobacteria to enhance the productivity and ef ficiency of P. edulis, emphasizing their value for commercial nursery applications and their contribution to more sustainable agriculture.